Crossmodal correspondences: Innate or learned? - Spence, C; Deroy, O (2012)
"Are Chimpanzees synaesthetic?" An affirmative answer to this question appeared recently in a Nature commentary on a study by Ludwig, Adachi, and Matzuzawa (2011) that demonstrated crossmodal correspondences in both chimpanzees and humans. Here we question the claim that chimpanzees are synaesthetic. We also question the claim that certain crossmodal correspondences are innate. We suggest an alternative account for the crossmodal correspondence between auditory pitch and visual lightness in terms of the internalization of correlations present in the environment. We highlight the limitations of such natural correlation approaches to the study of crossmodal correspondences as well as how such claims could potentially be tested in future research.